Governance in the Internet of Vehicles (IoV) context: examination of information privacy, transport anxiety, intention, and usage - Hussain, Hafezali Iqbal; Kamarudin, Fakarudin; Mohd-Sanusi, Zuraidah; Mohamed Shuhidan, Shuhaida; Al-Dhubaibi, Ahmed Abdullah Saad; Ahmad Razimi, Mohd Shahril (Hindawi Publishing, 2021)
This study examines the validity and acceptability of concern for information privacy with the Internet of vehicle context. For this purpose, the exploratory and confirmatory analysis processes were performed for testing the validity of concern for the Internet of vehicle information privacy. A total number of 357 responses were received online which were complete in all respects from college and university students studying information system course at undergraduate and graduate level. The estimated results obtained from exploratory and confirmatory factor analysis revealed that 3-dimension construct containing collection, error, and information accuracy measuring governance for Internet of vehicle information privacy (CFIOVIP) was validated through second order construction with strong goodness-of-fit estimates. The relevant factors were reliable and valid as per their internal and external validity estimates of Cronbach Alpha, average variance extracted, composite reliability, discriminant validity, and factor loading values including their fitness indices for 16 items for 3-dimension construct of CFIOVIP. The findings of the study indicate that Internet of vehicle users view secondary usage of information and unauthorised access of information as the same dimension with the title of information access for measuring CFIOVIP along with two other constructs like collection and error in information for the Internet of vehicle context. The study recommends a 2nd order CFIOVIP construct based on three dimensions, namely, collection, error, and information access, for testing the present governance of the Internet of vehicles.